(untitled) (Balthazar, 2025)
María Zambrano, a 20th-century Spanish philosopher and writer, engaged with the figure of Antigone across multiple contexts; in fact, the Sophoclean figure emerges as a recurring motif in her work, reinterpreted in accordance with her poetic vision and philosophical inquiry. This contribution aims to reconstruct the philosophical reflection developed by María Zambrano around the condition of exile, using Antigone as a central symbolic reference. Through a symbolic and poetic elaboration of this tragic character, Zambrano progressively develops a conception of exile that transcends its strictly historical dimension, gradually acquiring an anthropological and literary significance, in line with the interpretative categories proposed by José Luis Abellán. From this perspective, her work offers a genuine phenomenology of exile, where the biographical experience is interwoven with a broader ontological and philosophical meditation.